Adrian Encalada: capstone - Encalada, Adrian, artist (Colorado State University. Libraries, 2013)
The artist's statement: Commenting on time, sense of place, and the home, Bricks is a study of Art Deco style apartment buildings in the Capitol Hill area of Denver. Each building was influenced by the most prominent architect of the time, Charles Strong, and were all built between 1925 and 1960. The similarities in design link all the buildings to a time and place, but the subtle effects of time have made each one uniquely different. I was drawn to these buildings by their command of the space around them. Often butted up against the next building on the street, each one dominates their block and stands proudly, defiant of the ravages of time. This is my attempt to honor their legacy.
Bricks
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.